KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN SEARCH, FIND, AND CONSTRUCT TOGETHER (SFCT) PADA MATERI MATRIKS KELAS XI SMA NEGERI 2 MALANG - Tutut Noviyanti (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2019)
The purpose of this study was to determine whether there were differences in critical thinking skills and to describe critical thinking skills among students taught using the Search learning model, Find, And Construct Together (SFCT) and conventional learning models. The research method used is a combination research method with sequential explanatory design. Quantitative data samples were students of class XI MIPA 1 and XI MIPA 2, this quantitative research was obtained by testing students' critical thinking skills. Analysis of the data used is the t test with the prerequisite test, namely the normality test and homogeneity test. Qualitative research subjects were 9 students. The nine students were selected based on high, medium and low critical thinking skills. While the collection of qualitative data is done by observation, interviews, and field notes. The results showed that (1) Based on the results of quantitative data analysis with hypothesis testing using SPSS 20 software, the Sig 2-tailed value was obtained = 0.009. Because the Sig value = 0.009 <0.025 then H0 is rejected. This means that it can be concluded that there are significant differences in critical thinking skills between students who are taught by the SFCT learning model and students who were taught using conventional models. (2) Based on qualitative data analysis obtained from interviews, it can be concluded that students like to be taught using the SFCT model and as many as 80.56% of students fulfill four indicators of critical thinking, while students are not happy to be taught using conventional models and only 63.86% students who fulfill the four indicators of critical thinking.